A Study of Subway Marketing 4P Strategy - Varsha Ganatra; A.A. Gde Satia Utama; Puran Puran; Rudresh Pandey; Liang Mei Qi; Daisy Mui Hung Kee; Irene Saw Ai Ling; Lim Hooi Sien; Tan Jia Tien; Hafizh Sasining Ramadhan; Liem Gai Sin; Madhu Ashok Pandey (Asia Pacific Journal of Management and Education (APJME), 2021)
The purpose of this study is to examine Subway marketing 4P strategy as the competition in the fast-food industry is extremely high. Subway is needed to keep on striving for better performances to build existing customer loyalty while attracting new customers. Therefore, we examine Subway marketing 4P (product, price, promotion, and place) to ensure that Subway can obtain a competitive advantage in the marketplace. The study used primary and secondary data methods to collect respondents’ perceptions of Subway performances. The findings indicated that marketing 4P strategies are the important prediction of the success of the company.